Pengaplikasian Sistem Rumah Pintar pada Rumah Tinggal - Erwin Herlian; Adenimas Putri Wardani (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2024)
The concept of smart homes has revolutionized the way we interact with our living spaces, offering a myriad of benefits ranging from enhanced convenience to improved energy efficiency and security. This paper provides a overview of smart home technologies, their applications, and their impact on modern living. Firstly, we delve into the underlying principles of smart home systems, which typically integrate Internet of Things (IoT) devices, sensors, actuators, and connectivity solutions to create interconnected ecosystems. Secondly, we focus on the functionalities offered by smart home technologies. Advanced features such automatic lighting and security control. These features optimize user needs and experiences before built. Additionally, we address the challenges and considerations inherent in adopting smart home technologies, such as interoperability issues, privacy concerns, cybersecurity risks, and the digital divide. Effective deployment and integration strategies, along with robust privacy and security measures, are crucial for ensuring the reliability, scalability, and user acceptance of smart home ecosystems. In conclusion, the evolution of smart home technologies continues to redefine the way we inhabit and interact with our living spaces. As these systems become increasingly sophisticated and ubiquitous, they hold the potential to not only enhance our quality of life but also contribute to a more sustainable and connected future.